Safety, activity, and pharmacokinetics of GLQ223 in patients with AIDS and AIDS-related complex. - Kahn, J O (1994)
GLQ223 is a highly purified single-chain ribosome-inactivating protein with selective effects against a variety of cells, including macrophages infected with human immunodeficiency virus. We evaluated the safety, pharmacokinetics, and immunologic effects of multiple doses of GLQ223 in 22 patients with AIDS or AIDS-related complex; CD4+ T-cell counts were between 100 and 350/mm3. GLQ223 was administered intravenously at doses of 8, 16, 24, 36, and 50 micrograms/kg of body weight; the drug was administered by constant infusion over 3 h to achieve a concentration in serum of 50 ng/ml; this concentration is known to be associated with anti-HIV effects in vitro. All patients reported a flu-like syndrome characterized by muscle and joint aches and an increase in creatinine kinase levels; symptoms were controlled easily. For patients who received 36 and 50 micrograms/kg, target concentrations in serum were achieved and an increase in CD4+ and CD8+ T cells was sustained; this sustained increase persisted for at least 28 days after the last infusion. beta 2-Microglobulin levels increased during the infusions and then declined when the infusions ended. Repeat infusions of GLQ223 were safe and relatively well tolerated. The target concentration of GLQ223 in serum was achieved and sustained. Our results suggest that GLQ223 may have activity in treating patients with human immunodeficiency virus infection.